Facile access to a Ge(II) dication stabilized by isocyanides - Swamy, V. S. V. S. N.; Yadav, Sandeep; Pal, Shiv; Das, Tamal; Vanka, Kumar; Sen, Sakya S. (Chemical Communications, 2016)
Herein, we introduce isocyanide as a ligand in main group chemistry and describe the facile isolation of a Ge(II) dication. The reaction of 2,6-dimethylphenylisocyanide with GeCl2 leads to the formation of a Ge(II) dication with two [GeCl3](-) molecules as counter anions. The dicationic Ge(II) center is bound to four isocyanide ligands and also holds a lone pair of electrons. DFT calculations reveal that the dication is stabilized only by sigma-donation from the four isocyanide ligands. Natural population analysis gives a charge of +0.74 on the Ge(II) center, indicating that the positive charge is shared by the isocyanide substituents.